Actitudes lingüísticas del hablante cubano hacia el español de las Antillas - Roxana Sobrino Triana (Signo y Seña, 2016)
The article approaches the perceptions and linguistic attitudes of the Cuban towards the variants of Spanish in the Hispanic Antilles: Cuba, Puerto Rico and Dominican Republic. The investigation is based on a questionnaire done in the Cuban capital to 72 informants as part of a study that includes the three countries. Of the questionnaire 5 questions were selected for the analysis for the intention of investigating the way in which the Cuban of the capital perceives his own modality of language, the attitudes that they demonstrate towards the variants of his neighbors and the way in which they value the language in relation to the other two remaining ones. The results aim at (auto) linguistic discrimination in contraposition with strong samples of loyalty and linguistic pride. Likewise, there is a demonstrated sense of linguistic superiority of the Cuban in relation to Dominicans and Puerto Ricans.